Analisis Pelanggaran Strategi Pemasaran dalam Praktik Repackaging dan Overclaim Terhadap Keputusan Pembelian Skincare Lokal - Hanny Handayani; Halimah Zahrah; Windi Tri Natarina; Dessy Susilawati (Jejak digital: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze violations of marketing strategies through repackaging and overclaim practices in local skincare brands, with a case study on the Athena brand. Repackaging refers to the act of relabeling imported products without official authorization and selling them as if they were locally produced, thereby misleading consumers by creating a false sense of added value. Overclaim, on the other hand, involves exaggerated product benefit claims without scientific evidence or approval from the Indonesian FDA (BPOM). This research employs a descriptive qualitative method through literature review. The findings reveal that these practices significantly affect consumer purchasing decisions by manipulating perceptions and forming unrealistic expectations, especially when amplified by social media and influencers. Beyond economic impact, such practices violate health regulations and ethical principles, including Islamic values that emphasize honesty in trade. This study underscores the urgent need for ethical marketing strategies based on transparency, legality, and corporate social responsibility. Ethical marketing fosters long-term trust between producers and consumers while also preserving the credibility of the local skincare industry in Indonesia. Strengthening consumer literacy and regulatory enforcement is essential to combat misleading marketing and to promote a sustainable, responsible beauty market ecosystem.